Macroeconomic shocks, political stability and public policy: Determinants of tourism arrivals in Peru (2003-2023) - Bendezú-Jiménez, Héctor Javier; Romero Bendezú, Aníbal Erik; Ríos Delgado , Teresa Jesùs; López Sánchez, José Antonio (Investigaciones Turísticas, 2026)
Following the Toda-Yamamoto procedure, an augmented Vector Autoregression (VAR) model was estimated to conduct Granger non-causality tests. This paper explores how macroeconomic volatility—driven by oil prices, exchange rate fluctuations, political instability, and inflation—and public tourism policies, including PROMPERÚ’s promotional campaigns and COPESCO infrastructure projects, influenced international tourist arrivals to Peru (2003–2023). The results show that oil prices and exchange rate fluctuations significantly affect inbound tourism, highlighting cost sensitivity. Political instability—understood as negative shocks in the political stability index—temporarily reduces tourist arrivals, though its impact fades over time when countered by institutional credibility. PROMPERÚ’s campaigns show strong short-term effects that weaken without strategic renewal. COPESCO investments exhibit no significant short-term impact, revealing persistent infrastructure and coordination gaps. These findings highlight the need for an integrated tourism strategy that aligns macroeconomic stability, sustained promotion, and infrastructure planning. In a fast-evolving global market, enhancing Peru’s competitiveness will require stronger cross-sector collaboration and data-driven policymaking.